Bacillus anthracis - Fouch, Sarah (Henry Stewart Talks, 2025)
Characteristics of Bacillus anthracis, Transmission of Bacillus anthracis, Anthrax pathogenicity in human, Virulence factors, Anthrax toxins, Diagnosis and treatment